2018
DOI: 10.1111/jne.12485
|View full text |Cite
|
Sign up to set email alerts
|

Rapid actions of oestrogens and their receptors on memory acquisition and consolidation in females

Abstract: Increased attention has been paid in recent years to the ways in which oestrogens and oestrogen receptors rapidly affect learning and memory. These rapid effects occur within a timeframe that is too narrow for the classical genomic mode of action of oestrogen, thus suggesting nonclassical effects as underlying mechanisms. The present review examines recent developments in the study of the rapid effects of 17β- K E Y W O R D Scell signalling, nongenomic, object recognition, social learning, social recognition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 95 publications
(340 reference statements)
0
38
0
Order By: Relevance
“…These non-genomic mechanisms promote the rapid activation of different intracellular signaling pathways that ultimately may lead to neuroprotection. The best characterized pathway in neurons involves the activation of extracellular signal-regulated kinases (ERK) and phosphotidylinositol 3-kinase (PI3K)/Akt/glycogen synthase kinase 3 (GSK3) pathway in brain areas related to memory and cognition (Kelly and Levin, 2001 ; Marin et al, 2005 ; Garcia-Segura et al, 2006 ; Sheppard et al, 2017 ). In septal and hippocampal neurons, activation of PI3K/Akt/GSK3 signal transduction has been shown to protect against injuries induced by, Aβ exposure, glutamate exocytosis, staurosporine-induced apoptosis, and oxygen glucose deprivation (Marin et al, 2005 ; Zhao et al, 2016 ).…”
Section: Multifactorial Roles Of Estrogen Receptors In Brain Preservamentioning
confidence: 99%
“…These non-genomic mechanisms promote the rapid activation of different intracellular signaling pathways that ultimately may lead to neuroprotection. The best characterized pathway in neurons involves the activation of extracellular signal-regulated kinases (ERK) and phosphotidylinositol 3-kinase (PI3K)/Akt/glycogen synthase kinase 3 (GSK3) pathway in brain areas related to memory and cognition (Kelly and Levin, 2001 ; Marin et al, 2005 ; Garcia-Segura et al, 2006 ; Sheppard et al, 2017 ). In septal and hippocampal neurons, activation of PI3K/Akt/GSK3 signal transduction has been shown to protect against injuries induced by, Aβ exposure, glutamate exocytosis, staurosporine-induced apoptosis, and oxygen glucose deprivation (Marin et al, 2005 ; Zhao et al, 2016 ).…”
Section: Multifactorial Roles Of Estrogen Receptors In Brain Preservamentioning
confidence: 99%
“…Oestrogens were found to play a role in neuronal plasticity and spine synapse formation . Furthermore, many studies have shown positive effects of oestrogens on cognition . In Alzheimer's disease, oestrogens have been shown to protect neurones against the toxicity of amyloid plaques .…”
Section: Sex Steroid Hormones and Brain Functionmentioning
confidence: 99%
“…25,26 Furthermore, many studies have shown positive effects of oestrogens on cognition. [27][28][29] In Alzheimer's disease, oestrogens have been shown to protect neurones against the toxicity of amyloid plaques. 30 Nevertheless, more studies are necessary 31 because investigators from the Women's Health Initiative Memory Study found that therapy with a combination of oestrogen and progestin increased the risk for dementia in postmenopausal women and did not improve their performance in mild cognitive tasks.…”
Section: Sex Steroid Hormones and Brain Functionmentioning
confidence: 99%
“…Recent evidence from PELP1 forebrain‐specific knockout mice demonstrated a critical role of PELP1 in mediating both extranuclear and nuclear ER signalling in the brain, as well as 17β‐oestradiol‐induced neuroprotection, anti‐inflammatory effects and regulation of cognitive function . The review by Sheppard et al examines recent developments in the study of the rapid effects of 17β‐oestradiol and ER agonists on learning and memory tasks in female rodents, including the activation of intracellular signalling cascades and epigenetic processes.…”
mentioning
confidence: 99%
“…Recent evidence from PELP1 forebrain-specific knockout mice demonstrated a critical role of PELP1 in mediating both extranuclear and nuclear ER signalling in the brain, as well as 17β-oestradiol-induced neuroprotection, anti-inflammatory effects and regulation of cognitive function 18. The review by Sheppard et al19 examines recent developments in the study of the rapid effects of 17β-oestradiol and ER agonists on learning and memory tasks in female rodents, including the activation of intracellular signalling cascades and epigenetic processes.The rapid nongenomic modulation of dendritic spinogenesis in rat and mouse hippocampal slices is mediated by sex steroids, including dihydrotestosterone, testosterone, oestradiol and progesterone.These rapid synaptic modulations are mediated by sex steroid receptors, including rapid nongenomic effects. In the review by Murakami et al,20 the results from the optical imaging of dendritic spines are discussed, together with results obtained from other types of imaging techniques, including electron microscopic imaging.Relationships between spine modulation and the modulation of cognition are also discussed.…”
mentioning
confidence: 99%